Targeting Solid Tumors With BTK Inhibitors - Uckun, Fatih M.; Venkatachalam, Taracad (Frontiers in Cell and Developmental Biology, 2021)
The repurposing of FDA-approved Bruton’s tyrosine kinase (BTK) inhibitors as therapeutic agents for solid tumors may offer renewed hope for chemotherapy-resistant cancer patients. Here we review the emerging evidence regarding the clinical potential of BTK inhibitors in solid tumor therapy. The use of BTK inhibitors may through lead optimization and translational research lead to the development of new and effective combination regimens for metastatic and/or therapy-refractory solid tumor patients.